Platoon - Stone, Oliver; Hemdale Film Corporation; LIVE Entertainment (Firm).; Viva Vidoes Inc. (Van Nuys, Calif. LIVE Entertainment ; distributed in the Philippines by Viva Videos Inc., 2000)
The story of innocence lost in the war torn jungles of Vietnam as conflict between members of a single platoon unfolds.
Originally produced as a motion picture in 1986
Director, Oliver Stone ; producer, Arnold Kopelson ; writer, Oliver Stone ; original music, Georges Delerue ; executive producers, John Daly, Derek Gibson.
Charlie Sheen, Willem Dafoe, Tom Berenger, Forest Whitaker, Keith David, Francesco Quinn, Kevin Dillon, John C. McGinley.
VCD
Keywords: Vietnam War, 1961-1975 -- Drama; War films